Associations among neuroticism, self-efficacy, resilience and psychological distress in freshman nursing students: a cross-sectional study in China - Xiaoxiao Mei; Huiyuan Wang; Xinqin Wang; Xiaona Wu; Jieyi Wu; Zengjie Ye (BMJ Open)
Objectives The current study examines the mediating roles of resilience and self-efficacy and the moderating role of gender in the association between neuroticism and psychological distress in Chinese freshman nursing students (FNSs).Methods A total of 1220 FNSs were enrolled from the Be Resilient to Nursing Career (ChiCTR2000038693) Programme and the following instruments were administered to them: NEO Five-Factor Inventory, General Self-Efficacy Scale, Connor-Davidson Resilience Scale and Kessler Psychological Distress Scale. A moderated mediation analysis and a generalised additive model analysis were performed.Results The direct and indirect effects of neuroticism on psychological distress were significantly mediated by self-efficacy (B = 0.200, 95% CI 0.001 to 0.039), resilience (B = 0.021, 95% CI 0.007 to 0.038) and the interaction between self-efficacy and resilience (B = 0.016, 95% CI 0.005 to 0.028). The interactions between neuroticism and gender (β = 0.102, 95% CI 0.001 to 0.203, p<0.05) and between resilience and gender were significant (β = 0.160, 95% CI 0.045 to 0.275, p<0.01). A non-linear and positive association was confirmed between neuroticism and psychological distress.Conclusions Self-efficacy and resilience significantly mediate the relationship between neuroticism and psychological distress. Gender moderates the relationships between neuroticism and resilience and between resilience and psychological distress.